2018
DOI: 10.1371/journal.pone.0190699
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging reveals differences in brain activation in response to thermal stimuli in diabetic patients with and without diabetic peripheral neuropathy

Abstract: IntroductionDiabetes affects both the peripheral and central nervous systems. The aim of this study was to explore the changes in brain activity in response to thermal stimuli in diabetic patients with and without diabetic peripheral neuropathy (DPN) using functional magnetic resonance imaging (fMRI).MethodsA total of 36 right-handed volunteers were enrolled: eight patients with Type-2 diabetes mellitus and DPN, 13 patients with Type-2 diabetes mellitus lacking DPN (NDPN patients), and 15 healthy volunteers (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…We also observed altered WM in the corticospinal tract, internal capsule, spinothalamic tract, and thalamocortical projecting fibers. Physiologically, the somatosensory cortex, together with the thalamus, spinothalamic tract, and thalamocortical projecting fibers, make up an important component of the somatosensory pathway that governs the central integration and modulation of various peripheral sensations (Li et al, ). The precentral gyrus, paracentral lobule, caudate/putamen (known as the neostriatum), medial pallidum, thalamus, and corticospinal tract/internal capsule constitute a neural pathway that functions in coordinating voluntary movement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed altered WM in the corticospinal tract, internal capsule, spinothalamic tract, and thalamocortical projecting fibers. Physiologically, the somatosensory cortex, together with the thalamus, spinothalamic tract, and thalamocortical projecting fibers, make up an important component of the somatosensory pathway that governs the central integration and modulation of various peripheral sensations (Li et al, ). The precentral gyrus, paracentral lobule, caudate/putamen (known as the neostriatum), medial pallidum, thalamus, and corticospinal tract/internal capsule constitute a neural pathway that functions in coordinating voluntary movement.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, using magnetic resonance spectroscopy, Selvarajah et al () observed a significantly lower N ‐acetyl aspartate to creatine ratio in the thalamus of patients with DPN, suggesting thalamic neuronal dysfunction. One task‐based fMRI study (Li et al ) found that after several sessions applying thermal stimuli to the lower extremities, patients with DPN showed stronger brain activation in somatosensory pathways (e.g., in the right insula and left caudate nucleus) than healthy volunteers or diabetic patients without DPN. A multimodal study combining blood oxygenation level‐dependent and arterial spin labeling data (Segerdahl, Themistocleous, Fido, Bennett, & Tracey, ) reported altered ventrolateral periaqueductal gray (PAG) functional connectivity in patients suffering from painful DPN, and suggested this could be an index of brain‐based pain facilitation for painful DPN.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, emerging evidence has indicated central nervous system involvement in DPN, and the association between cognitive impairment and DPN in diabetes had been reported [40][41][42]. It is suggested that dysregulation of glycemic control may lead to microvascular dysfunction in the blood-brain barrier, autoimmune damage to neurologic diseases, and changes in the synthesis, availability, or reuptake of neurotransmitters.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to frontal regions, hereditary neuropathy has been associated with white matter disturbances in frontal regions (Wang et al, 2015); both chemotherapy-induced (Boland et al, 2014, Nudelman et al, 2016) and diabetic (Li et al, 2018, Manor et al, 2012) neuropathies show altered frontal activity. Furthermore, frontoparietal regions are relevant to encoding vibrotactile stimuli (Woolgar and Zopf, 2017) (see also, Godde et al, 2010, Wu et al, 2018, Fassihi et al, 2017, Ku et al, 2007, Soros et al., 2007).…”
Section: Discussionmentioning
confidence: 99%